Effects of some compounds on the A-Amylase Activity Purified From Abena-24 Wheat Flour Treated by TriboliumConfusum - M. Ismail (College of Education for Pure Sciences, 2005)
a-Ainylase was purified from Abena-24 wheat flour treated by Triboliumconfusuminsect using heat treatment, ammonium sulphateprecipitation, dialysis, and anion exchange chromatography. Three a-amylase isoenzymes were isolated (I, II and III) with elution volume of 90, 170 and 220 ml respectively, with specific activity of 73000, 185818 and 462333 mu/mg protein, respectively compared with the crude enzyme. Many compounds showed different effects on the a-amylase isoenzymes activity. Pheriyl .hydrazine, EDTA and HC1 showed an inhibitory effect between (70-80%), (49-53.5%) and (46.4-67.5%) respectively. Using heavy metales , it was observed that Cu+2 caused an inhibitory effect between (32.8-42,2%>), while Fe+2 caused an inhibitory effect between (26.3-53.5%). On the other hand, no significant inhibitory effect was shown with iodoacetamide and tristearin. Chloride ion and calcium ion showed an activitory effects on the a-amylase isoenzymes 1, II and III ranging between. (27-45.4%) for CI" and (15-82%) for Ca+J